2005
DOI: 10.1108/14777260510592103
|View full text |Cite
|
Sign up to set email alerts
|

General practitioner non‐principals benefit from flexible working

Abstract: This was the first time a study of all non-principals in Scotland had been attempted. The findings provide a more comprehensive picture of GPs in Scotland and provide valuable information for policymakers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
(13 reference statements)
2
8
0
Order By: Relevance
“…As in other studies [1,9], we find evidence of preference heterogeneity for different organisational characteristics, and there is evidence that different types of GPs attach different values to hours of work. Further, the finding that increased working hours generates disutility is in line with the earlier evidence of preferences for more flexible hours [12]. Moreover, our study provides evidence that the majority of GPs feel under time pressure and feel that they work too much.…”
Section: Consistency With Findings From Earlier Studiessupporting
confidence: 89%
See 2 more Smart Citations
“…As in other studies [1,9], we find evidence of preference heterogeneity for different organisational characteristics, and there is evidence that different types of GPs attach different values to hours of work. Further, the finding that increased working hours generates disutility is in line with the earlier evidence of preferences for more flexible hours [12]. Moreover, our study provides evidence that the majority of GPs feel under time pressure and feel that they work too much.…”
Section: Consistency With Findings From Earlier Studiessupporting
confidence: 89%
“…In addition, a number of job satisfaction surveys have been conducted for GPs in the UK including some organisational characteristics such as working hours, physical working conditions, remuneration, etc. [12][13][14]. These studies found among other things that extended possibilities of flexible working hours would be valuable; that job and personal characteristics of the GPs have an effect on job satisfaction; and that the most frequent factors of job stress was increasing workload, paperwork and insufficient time to do justice to the job.…”
Section: Previous Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Research has also shown the association of organizational characteristics of primary care with satisfaction of primary care providers [ 13 ]. A survey performed in England revealed that salaried physicians compared to self-employed GPs, experienced resentment due to difference in status, decision-making autonomy and type of work they performed in practice [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Working on shifts less adapted to family needs (with care-giving outside regular working hours or night shifts) is shown to be less desirable for the professional, as has been mentioned [2,29,30]. This is congruent with the fact that persons who live according to relationship models other than the stable couple have fewer adaptability problems and perceive better PQL.…”
Section: Discussionmentioning
confidence: 72%